KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS X SMA PELITA BANGUN REJO LAMPUNG TENGAH TAHUN PELAJARAN 2010/2011 - cici widiawati; mulyanto widodo; karomani karomani (FKIP Universitas Lampung, 2013)
The Problem in this research was the abilyty to write a description of the high school students of class X Bangun Rejo Pelita High Scholl Central Lampung Academic Year 2010/2011. This study aims to describe about the students skills in writing essays description.The method used in this reseach is a method of description. The population in this study were high school students of class X Pelita High School of Bangun Rejo Central Lampung Academic Year 2010/2011, amounting to 153 students spread over 4 classes. Samples were taken 15% of each class, so that the sample amounted to 23 students drawn randomly. The data is taken through a written test. Test such as essay writing task description with the experience they have.The results showed that mean score of the overall results of essay writing skills test descriptions Pelita high school students class X Bangun Rejo Central Lampung Academic Year 2010/2011 is 63,5% classified enough. The average capacity of each aspect are (1) the background of the title selection category excellent93,4%, (2) the accuracy of the posts with 60% categorized enough title, (3) similarity of the writing object category less 47,74%, (4) creating the impression readers categorized less 57,39%, (5) uncategorized outline less 58,28%, (6) a description of the facts in the sentence category enough 71,30%, (7) development of a sentence to paragraph 40,87% less uncategorized, (8) the preparation of a compotions paragraph description of 78,26% categorizedgood, (9) 44,35% effective sentence categorized less, (10) 77,39% categoryzed vocabulary good, (11) 70,43% categorized spelling enough, (12) the use of punctuation 69,57% categorized enough. From the results of the study can also be seen that the background for the selection of titles aspects are at the highest percentage is 93,4% and in the category of very good.Based on these results it can be concluded that the ability to write a description of the high scholl students of class X Pelita Bangun Rejo Central Lampung Academic Year 2010/2011 clasified as category enoughwith 63,5% and the percentage of outages drift interval 60%-74%.Keywords:Ability to Write, EssayDescription, Grade Student X.